Bahagian Jalan, Jabatan Kerja Raya Negeri Selangor / Nurul Syuhada Ahmad - Ahmad, Nurul Syuhada (Faculty of Civil Engineering, 2015)
Civil Engineering students of semester 4, 2015 of Faculty of Civil Engineering, University Technology Mara are required to undergo an Industrial Training for 7 weeks on the semester break of after finished final examination of Part4. The period of Industrial Training commence on 20 APRIL 2014 and completed on 5 JUNE 2014. Industrial training main intention is to expose the students to real-life experiences of the engineering works and to get them involved in Civil Engineering projects before graduate. It is one of the requirements for the award of Diploma in Civil Engineering is that the students MUST complete at least eight (7) weeks of industrial training. Industrial training is usually collected during the semester break at the end of the third year student (semester 4 and above). The technical and non-technical outcomes of the course may be assessed and evaluated through this industrial training. The industrial training can be used in colleting important information on civil engineering field that can be used later on as a review or guidance. With this training, I can introduce to the society on how the Civil Engineering Course by University Technology Mara (UiTM) works. To increase the level of graduates able to work, industrial training program was introduced to strengthen the competencies required. Industrial training course give students learning opportunities in the world of work to receive practical experience in order to improve the reliability of the market. We can also say that, the faculty intended to give the students an understanding on how the field of civil engineering is work. Industrial training can provide the students to have a new experience and with commitment from all side, these can give a long term benefits them during this industrial training period. The most important thing is what the students give during the training, that is the main key on what the resulted will turn to be. This automatically can also enhanced and boost their talent in civil engineering field for their future needs.